Toward an Indigenous, Decolonizing School Leadership: A Literature Review. (October 2019) - Khalifa, Muhammad A.; Khalil, Deena; Marsh, Tyson E. J.; Halloran, Clare
Background: The colonial origins of schooling and the implications these origins have on leadership is missing from educational leadership literature. Indeed little has been published on decolonizing and indigenous ways of leading schools.Purpose: In this article, we synthesize the literature on indigenous, decolonizing education leadership values and practices across national and international spaces that have been informed to various degrees by colonial models of schooling.Methodology: Through a review of the research and keywords including colonialism, educational leadership, indigenous communities, and decolonization, we identify two overarching themes.Findings: First, we found that the literature revealed a critique of the way in which Westernized Eurocentric schooling serves as a tool of imperialism, colonization, and control in the education of Indigenous peoples. Second, we discovered that the literature provided unique, but overlapping worldviews that situate the values and approaches enacted by Indigenous leaders throughout the globe. Within this second theme, we identify five strands of an Indigenous, Decolonizing School Leadership (IDSL) framework that can contribute to the development and reflection of school leadership scholars and practitioners. Specifically, we found that the five consistent and identifiable strands across IDSL include prioritizing Indigenous ancestral knowledge, enacting self-reflection and self-determination, connecting with and empowering the community, altruism, and spirituality as expressed through servant leadership, and inclusive communication practices.Conclusion: Based on the identified worldviews and values, we conclude by offering insights on the structure and policy of post-colonial schooling, as well as implications for the theory, research and practice needed to reclaim the co-opted contributions of Indigenous leaders in ways that decenter Western colonial approaches to leadership.